PREDICTION OF MULTIFOCAL ATHEROSCLEROSIS IN WOMEN WITH RHEUMATOID ARTHRITIS - I. V. Osipova; Yu. N. Starodubova; О. N. Antropova (Российский кардиологический журнал)
Aim. To define the most common localization and risk factors for multifocal atherosclerosis in females with rheumatoid arthritis (RA).Material and methods. At first stage, retrospectively an analysis of medical documentation was done, of 245 RA female patients. For the second stage conducted as a prospective observation, case histories of 105 women included, comparable by age, duration of RA. Participants were selected to 2 groups: 1st (n=49) — with clinically manifest atherosclerosis, 2nd (n=56) — with none. Analysis of cardiovascular risk factors was done and chronic inflammation markers.Results. In all atherosclerosis patients there was multifocal lesion (n=49). Common localizations are coronary arteries (81,7%) with involved lower extremities lesion (59,2%) and/or carotid arteries (69,3%). In the 1st group, there were more common arterial hypertension (AH) (100 and 64%, p=0,009), psychosocial risk factors (39 and 5%, p=0,001), pre-eclampsia or eclampsia anamnesis (38 and 11%, p=0,01), raise of total cholesterol (TC) (67 and 55%, p=0,01). In the 1st group, the markers of inflammation were raised more commonly, p<0,05. As a statistically significant predictors of multifocal atherosclerosis development in RA female patients play role age, AH, sleep disorder, depression, high activity of RA, early menopause, raise of TC, prednisolone intake. There was negative correlation revealed of low density lipoproteides cholesterol increase and atherosclerosis development, p=0,04.Conclusion. The specifics of atherosclerosis in RA is its multifocal lesion. Mathematic model that has been introduced, is based upon multifactorial analysis and can be recommended as a method for prediction of multifocal atherosclerosis. Predictor complex revealing for multivessel lesion and correction of modifiable risk factors should be the fundamental of prevention and cardiovascular risk reduction in RA female patients.